Formation of a combined electron-hole emission state in the LiRbSO4 – Eu phosphor - Т.Н. Нурахметов; Р.З. Бахтизин; Д.А. Толеков; Р.К. Шамиева; Ж.М. Салиходжа; Б.М. Садыкова; Б.Н. Юсупбекова; С.А. Пазылбек; Г.Б. Байрбаева; Б.М. Рахымжанов (Қарағанды университетінің хабаршысы. Физика сериясы)
In the irradiated phosphor 4 LiRbSO Eu , the mechanisms of formation of the induced or combined electron-emitting state at 3.1-2.94 eV were studied using optical and thermal activation spectroscopy methods. It has been shown experimentally that the combined electron-emitting state of the phosphor is formed from the electron states of impurity and intrinsic electron and hole trapping centers of 24Eu SO   and 34 4 SO SO . Electron and hole trapping centers are created by irradiating the phosphor with photons exceeding the width of the forbidden band of the matrix, where free electrons are created in the conduction band and a hole in the valence band. The trapping center is formed by the capture of free electrons by impurities and anionic complexes according to the reaction 3 2 Eu e Eu      ,2 34 4 SO e SO    . In one process with electron centers, holes in the form of 24SO are localized. Thus, impurity and intrinsic 2 4Eu SO   and 34 4 SO SO  electron-hole trapping centers are formed. Similarly, trapping centers are formed as a result of charge transfer from the excited anion of the 24SO complex to the 3Eu  impurities and to the neighboring 2 4 SO anions according to the reaction ( 2 3 O Eu   ) and ( 2 24O SO  ), and localized holes are also formed in one act along with it. Combined electron-emitting states consisting of impurity and intrinsic electron states are excited by photons with energies of ~4.0 eV and ~4.5 eV.